2003
DOI: 10.1016/s0960-9822(03)00580-3
|View full text |Cite
|
Sign up to set email alerts
|

PIR121 Regulates Pseudopod Dynamics and SCAR Activity in Dictyostelium

Abstract: Our results demonstrate a genetic connection between the pirA and scar genes. PIR121 appears to inhibit the activity of SCAR in the absence of activating signals. The location of the newly formed protrusions indicates that unregulated SCAR is acting at the edges of existing pseudopods, not elsewhere in the cell. We suggest that active SCAR protein released from the inhibitory complex is rapidly removed and that this is an important and novel mechanism for controlling actin dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
152
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(167 citation statements)
references
References 37 publications
(3 reference statements)
14
152
1
Order By: Relevance
“…S4 E and H). Because there are presently no convenient means to test this prediction pharmacologically, we studied a null mutant of PIR121, a component of the SCAR/WAVE complex, that is known to exhibit an excessive amount of polymerized actin (32). We found that occurrence of PIP3 nucleation was markedly enhanced in the mutant as expected (Fig.…”
Section: Phase-map Analysis Reveals Birth and Death Of Spatial Phasementioning
confidence: 72%
“…S4 E and H). Because there are presently no convenient means to test this prediction pharmacologically, we studied a null mutant of PIR121, a component of the SCAR/WAVE complex, that is known to exhibit an excessive amount of polymerized actin (32). We found that occurrence of PIP3 nucleation was markedly enhanced in the mutant as expected (Fig.…”
Section: Phase-map Analysis Reveals Birth and Death Of Spatial Phasementioning
confidence: 72%
“…Previous models suggested that WAVE/SCAR proteins act downstream of PIP 3 to regulate actin polymerization through the Arp2/3 complex. However, recent findings indicate that the SCAR complex is not required for chemoattractant-induced actin polymerization, suggesting an important role for other proteins (2). Finally, we may also have a very limited understanding of the complexity of the signaling pathways involved in chemotaxis.…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, recent genetic evidence indicates that this structure of complex is also important for the regulation of invertebrate Wave proteins, known as Scar proteins. Indeed, inactivation of the Sra homolog in Dictyostelium or of Sra, Nap, and Abi homologs in Drosophila leads in both cases to Scar͞Wave phenotypes (18)(19)(20)(21). In addition, in both systems, on genetic removal of the subunits, Scar͞Wave is degraded.…”
Section: Discussionmentioning
confidence: 99%